Life as Self-Maintenance - Wandschneider, Dieter (ETHICS IN PROGRESS, 2025)
The article constructs the organism as a living being and – unlike an automaton – as an individual concerned with its own self-maintenance, endowed with intrinsic purposiveness, autoregulation, and with an agency of the self as well. This is done from the perspective of the philosophy of organism developed by Kant, Hegel, and Plessner, and subsequently in the light of Systems Theory. Hegel’s Philosophy of Nature proves to be best suited to emancipate the contemporary, comprehensive concept of organism and its selfhood. To put it with Hegel’s words, it ‘is the Concept that comes into reality’ here.